Impact of Digital Distractions on Time Management Skills among Pokhara University Undergraduate Business Students in Kathmandu - Sah, Manisha Kumari (Nepalese Journal of Management, 2025)
This study examines the impact of digital distractions on time management skills among Pokhara university undergraduate business students in Kathmandu. Time management skills is the dependable variables. The independent variables are multitasking, social media usage, self-regulation, friends circle and device usage. The study is based on primary data with 155 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the Impact of digital distractions on time management skills among Pokhara university undergraduate business students in Kathmandu. The study showed that multitasking is positively correlated to time management skills. It means that increase in multitasking aspect of digital distractions leads to increase in positive time management skills. Likewise, social media usage is positively correlated to time management skills. It implies that digital distraction using social media results to increases in the time management skills. Similarly, self-regulation has a positive relationship with time management skills indicating that increase in the self-regulation aspect leads to increase in time management skills. Furthermore, friends circle has a positive relationship with time management skills. It implies that better friend circle leads to increase in time management skills. Likewise, device usage is positively correlated to the time management skills indicating that higher the device usage, higher will be the time management skills.